Increasing The Effectiveness Of Teaching History Through Miniature Art Works - et. al., Sulaymonov Askarali, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The article provides an important source of historical education - a theoretical basis for a new pedagogical approach to the didactic potential of miniature art. Also, on the basis of the study and analysis in the context of various facts, using the works of miniature art, the didactic basis for teaching the science of history on the optimal content and methodology was created. The article explores the concept of history education and the essence of the guidelines of the State Education Standard, updating and improving the didactic requirements for textbooks and manuals in the use of works of miniature art, selected on the basis of specific didactic requirements and methodological recommendations for use in history determined by the output.